Urban First Nations grandmothers : health promotion roles in family and community - Ginn, Carla S.; University of Lethbridge. Faculty of Health Sciences (Lethbridge, Alta. : University of Lethbridge, Faculty of Health Sciences, c2009, 2009)
ix, 146 leaves 29 cm The purpose of this participatory action research study was to gain an awareness of the meanings of health for urban First Nations grandmothers, and how they promote it in their families and communities. Active participation of 7 urban First Nations grandmothers in the research process involved 4 group and 1 individual interview. Meanings of health included maintaining balance in all areas of life; physical, mental, emotional, and spiritual. Control imposed through the residential schools resulted in secrets kept, yet the survival and resiliency of the grandmothers were identified as part of being healthy. Personal health was linked with the health of their families and communities, and an awareness of living in two cultures vital in the intergenerational transmission of knowledge. Relationships with grandchildren were catalysts for change, and the grandmothers described working to “turn it around” throughout their challenges in health and life, as one strategy for health promotion.